Nonselective Chemical Inhibition of Sec7 Domain-Containing ARF GTPase Exchange Factors. Issue 10 (17th July 2018) - Mishev, Kiril; Lu, Qing; Denoo, Bram; Peurois, François; Dejonghe, Wim; Hullaert, Jan; De Rycke, Riet; Boeren, Sjef; Bretou, Marine; De Munck, Steven; Sharma, Isha; Goodman, Kaija; et al.
Abstract : A chemical genetic approach uncovered the small molecule Secdin, which impairs multiple endomembrane trafficking routes by targeting the Arabidopsis ARF GTPase exchange factors. Abstract: Small GTP-binding proteins from the ADP-ribosylation factor (ARF) family are important regulators of vesicle formation and cellular trafficking in all eukaryotes. ARF activation is accomplished by a protein family of guanine nucleotide exchange factors (GEFs) that contain a conserved catalytic Sec7 domain. Here, we identified and characterized Secdin, a small-molecule inhibitor of Arabidopsis thaliana ARF-GEFs. Secdin application caused aberrant retention of plasma membrane (PM) proteins in late endosomal compartments, enhanced vacuolar degradation, impaired protein recycling, and delayed secretion and endocytosis. Combined treatments with Secdin and the known ARF-GEF inhibitor Brefeldin A (BFA) prevented the BFA-induced PM stabilization of the ARF-GEF GNOM, impaired its translocation from the Golgi to the trans -Golgi network/early endosomes, and led to the formation of hybrid endomembrane compartments reminiscent of those in ARF-GEF-deficient mutants. Drug affinity-responsive target stability assays revealed that Secdin, unlike BFA, targeted all examined Arabidopsis ARF-GEFs, but that the interaction was probably not mediated by the Sec7 domain because Secdin did not interfere with the Sec7 domain-mediated ARF activation. These results show that Secdin and BFA affect their protein targets through distinct mechanisms, in turn showing the usefulness of Secdin in studies in which ARF-GEF-dependent endomembrane transport cannot be manipulated with BFA.